2023
DOI: 10.1002/anie.202302266
|View full text |Cite
|
Sign up to set email alerts
|

A Fused [5]Helicene Dimer with a Figure‐Eight Topology: Synthesis, Chiral Resolution, and Electronic Properties

Abstract: Chiral shape‐persistent molecular nanocarbons are promising chiroptical materials; their synthesis, however, remains a big challenge. Herein, we report the facile synthesis and chiral resolution of a double‐stranded figure‐eight carbon nanobelt 1 in which two [5]helicene units are fused together. Two synthetic routes were developed, and, in particular, a strategy involving Suzuki coupling‐mediated macrocyclization followed by Bi(OTf)3‐catalyzed cyclization of vinyl ether turned out to be the most efficient. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…As an added note, during the review of this article, the facile synthesis of an n-butoxy-substituted [16]K-infinitene was reported. 112 We found that the molecular structure identified by X-ray crystallography corresponds exactly to the lowest-energy isomer of [16]infinitenes, [1,2,1,1,2,1|1,1,2,1,1,2](−1), as predicted in this work. Furthermore, we might find certain infinitene structures, among a multitude of proposed candidates, that possess enhanced or desirable properties.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As an added note, during the review of this article, the facile synthesis of an n-butoxy-substituted [16]K-infinitene was reported. 112 We found that the molecular structure identified by X-ray crystallography corresponds exactly to the lowest-energy isomer of [16]infinitenes, [1,2,1,1,2,1|1,1,2,1,1,2](−1), as predicted in this work. Furthermore, we might find certain infinitene structures, among a multitude of proposed candidates, that possess enhanced or desirable properties.…”
Section: Discussionsupporting
confidence: 83%
“…With recent advances in the synthesis of looped polyarenes and in expanding kekulene and helicenes, we are confident to anticipate the expansion from the known [12] or [20]­infinitene to larger infinitenes in the foreseeable future. As an added note, during the review of this article, the facile synthesis of an n -butoxy-substituted [16]­K-infinitene was reported . We found that the molecular structure identified by X-ray crystallography corresponds exactly to the lowest-energy isomer of [16]­infinitenes, [1,2,1,1,2,1|1,1,2,1,1,2](−1), as predicted in this work.…”
Section: Discussionsupporting
confidence: 81%
“…The situation is common among [6]helicenes or smaller analogues 14,37,38,44,45,48,50,51,77 and may be tackled by different structural designs, such as double-helicenes, S-shaped or 8-shaped helical conjugated systems, elongated or extended helicenes. 46,77–84 Interestingly enough, in several of the just mentioned reports, the molecular design was steered by a preliminary computational screening, which confirms the demand for accurate computational approaches for property predictions.…”
Section: Resultsmentioning
confidence: 76%
“…Since this report, fascinating properties of infinitene have been predicted. 70−78 Wu and Isobe et al synthesized a twisted CNB in 2021 and a fused [5]helicene dimer in 2023 79,80 as a related molecule of infinitene. In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported.…”
Section: ■ Recent History Of Carbon Nanobeltsmentioning
confidence: 99%